The Effect of Work Discipline, Motivation and Education on ASN Performance at the Kaur Regency Bappeda - Fitra Rizki Yanuswan; Sulisti Afriani; Yudi Irawan Abi (Universitas Dehasen Bengkulu, 2023)
Performance is a measure of employees in carrying out the tasks targeted to be completed. Efforts to conduct performance assessments are important by knowing the right performance measurements. To improve the performance must pay attention to work discipline, motivation and education. This study aims to determine the effect of work discipline, motivation and education on Civil Servants performance at BAPPEDA of Kaur Regency. This type of research is quantitative, the sample in this study were 44 of Civil Servants at BAPPEDA of Kaur Regency. Data collection used a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of this research show that the regression equation is 1.338 + 0.224X1 + 0.411 X2 + 0.344X3 + 4.297 (e). the coefficient of determination of R square is 0.831. This means that X1 (work discipline), X2 (motivation), X3 (education) have a contribution to performance (Y) of 83.1% while the remaining 16.9% is influenced by other variables not examined in this study. The test results for variable X1 (work discipline) show a significant value of 0.007<0.05. This means that X1 (work discipline) has a positive and significant effect on performance (Y). X2 variable (Motivation) shows a significant value of 0.000<0.05. This means that X2 (Motivation) has a positive and significant effect on performance (Y). The variable X3 (education) shows a significant value of 0.001<0.05. This means that X3 (education) has a positive and significant effect on performance (Y). The results of the simultaneous hypothesis calculations show a significant value of 0.000 <0.05, meaning that together X1 (work discipline), X2 (motivation), X3 (education) have a positive and significant effect on performance (Y ).